Kinematic evolution of the Pieniny Klippen Belt in Cenozoic (Ukrainian Carpathians) - Murovskaya, A. V.; Nakapelyukh, M. V.; Vikhot, Yu. M.; Shlapinskiy, V. E.; Bubnyak, I. N.; Mychak, S. V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2016)
The data on surface, subsurface and deep structure of the Pieniny Klippen Belt (PKB) have been summarized and new results of its geological-structural and fault kinematic studies within the Ukrainian part of the Eastern Carpathians have been presented. In its contemporary appearance as a narrow strongly tectonized zone between the Outer Carpathians and Trans-Carpathian trough PKB was formed in Oligocene—Miocene in the place of ancient ocean. On the surface it is situated within the rootless Pieniny nappe and in the deep it is a steeply dipping deformation zone which developed under compression, simple dextral strike-slip, transtension and transpression. Mesostructures of horizontal shortening and vertical elongation, thrusts and thrust-related folds as well as structures of lateral extrusion — dextral strike-slip along sub-meridional slicken-sides correspond to SW—NE 220° trending compression and correlate with the stage of Alcapa microplate progression in NE direction in Oligocene—Early Miocene. In Early Miocene as a result of counter-clockwork rotation of Alcapa dextral strike-slip deformation is concentrated in boundary zone between Alcapa and accretionary prism of Ukrainian Flysch Carpathians. The stress fields of strike-slip type with orientation of compression axis SE 165—SW 215° and its “rotation” in a zone of simple shear correspond to this stage. Present deformation regime is characterized as transpressure with SW—NE orientation of compression axis.